Closing the Gap Between Education and Labor Market Requirement: Do Vocational Education Matter? - FX Gugus Febri Putranto; Christiayu Natalia; Ni Kadek Dian Pitriyani (The Journal of Indonesia Sustainable Development Planning, 2024)
The alignment between educational attainment and job type is expected to create a win-win solution from both the labor supply and demand perspectives. Despite these expectations, challenges remain in fully realizing such alignment within labor markets. In Indonesia, vertical mismatch continues to be a significant concern, particularly among the youth. Vocational education is predicted to be able to close that gap. This study aims to (1) analyze the impacts of vocational education toward vertical mismatch and (2) examine the impact of vertical mismatch on decent income among young people in Indonesia. Using Sakernas microdata analyzed using logistic regression method, the study finds that youth who complete vocational education are less likely to experience vertical mismatch. Furthermore, youth who are matched or overeducated have higher chances of earning a decent income. These findings underscore the needs of vocational education curriculum aligned with labor market demands.